Pengaruh Latihan Diamond Passing terhadap Ketepatan Passing Futsal (Studi Eksperimen pada Peserta Ekstrakulikuler Futsal SMK Negeri 1 Blora) - Pratama, Miftakhul Khusna Dizki; Indarto, Pungki; Syaukani, Agam Akhmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to measure the influence and how significant the impact of diamond passing training is on the passing ability of students who take part in the futsal extracurricular at SMK Negeri 1 Blora. The research was conducted on 29 July - 10 September 2024 at SMK Negeri 1 Blora. The sampling method was carried out using a purposive sampling method with a sample size of 20 students. Data was obtained through pre-test and post-test. The analytical methods used are the normality test, homogeneity test, and t-test to test the hypothesis. The research results show that Diamond Passing in futsal passing can have a significant impact with a value of 0.000<0.05. This shows that there is an influence and it can be seen that the tcount>ttable value is 5.140>1.724, showing that Diamond Passing practice has an impact or influence on passing. futsal extracurricular students at SMK Negeri 1 Blora. In conclusion, there is an influence of diamond passing training on the passing ability of students who take part in extracurricular futsal. Keywords: diamond passing, futsal, passing